Inclusive Education in Technical University - G. Savka, O.; V. Milkina, E. (International Journal of Engineering and Technology, 2018)
Â The present article addresses the issue of importance of inclusive education in higher education institutions with statistical data on students with disabilities undergoing training. In this article the problems of university readiness for implementation of inclusive education of young people with disabilities are analyzed; and the legal, educational and systemic aspects of special education are investigated.Â Â